2018
DOI: 10.1186/s12884-017-1651-7
|View full text |Cite
|
Sign up to set email alerts
|

Valuing breastfeeding: a qualitative study of women’s experiences of a financial incentive scheme for breastfeeding

Abstract: BackgroundA cluster randomised controlled trial of a financial incentive for breastfeeding conducted in areas with low breastfeeding rates in the UK reported a statistically significant increase in breastfeeding at 6–8 weeks. In this paper we report an analysis of interviews with women eligible for the scheme, exploring their experiences and perceptions of the scheme and its impact on breastfeeding to support the interpretation of the results of the trial.MethodsSemi-structured interviews were carried out with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…140 No previous research has studied the effectiveness of CCTs in increasing lactation rates for mothers of VLBW infants; however, several recent studies have examined whether CCTs and other financial incentives are effective strategies for increasing breastfeeding rates in term infants. [141][142][143][144][145] One RCT from the United Kingdom enrolled mothers who resided in communities with lower than the country's average SES and baseline breastfeeding rates. This study revealed higher rates of any but not of exclusive breastfeeding in the CCT group (receiving £200 total) at 6-8 weeks post-birth.…”
Section: Strategies For Mitigating Economic Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…140 No previous research has studied the effectiveness of CCTs in increasing lactation rates for mothers of VLBW infants; however, several recent studies have examined whether CCTs and other financial incentives are effective strategies for increasing breastfeeding rates in term infants. [141][142][143][144][145] One RCT from the United Kingdom enrolled mothers who resided in communities with lower than the country's average SES and baseline breastfeeding rates. This study revealed higher rates of any but not of exclusive breastfeeding in the CCT group (receiving £200 total) at 6-8 weeks post-birth.…”
Section: Strategies For Mitigating Economic Barriersmentioning
confidence: 99%
“…141 The CCT had no effect on mothers' decisions to initiate lactation, but mothers perceived CCT as showing "value" for breastfeeding, compensating for ongoing breastfeeding challenges and facilitating achievement of targeted breastfeeding milestones (e.g., 6 weeks, 3 months). 145 Research on the use of financial incentives to increase breastfeeding in healthy but primarily disadvantaged populations reveal that mothers value cash or cash equivalents more than other financial incentives such as grocery vouchers or baby supplies, 145,146 and healthcare providers are generally positive but cautioned about choosing the proper incentive. [147][148][149] One small US study randomized 36 Puerto Rican mothers of healthy term infants to receive either WIC-only or WIC + CCT (≤$270 total over 6 months) and found that mothers in the WIC + CCT group had significantly higher rates of any but not of exclusive breastfeeding at 1 (89% vs 44%), 3 (89% vs 17%) and 6 (72% vs 0%) months post-birth.…”
Section: Strategies For Mitigating Economic Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we do not report on women's perspectives of the NOSH scheme; however, these views have been sought as part of the wider study (Relton et al, 2016) and are reported in a separate article (Johnson et al, 2018). We aimed to interview HCPs involved in delivering the NOSH scheme, and our recruitment strategy was based on those with most experience of the scheme-those who had signed the most application and claim forms.…”
Section: Limitationsmentioning
confidence: 99%
“…Over the past several decades, neonatal scholars have made their own recommendations to increase caregiver and community capacities (i.e., time and commitment to the infant, resources, caregiving skills and knowledge) and buffer infant stress. Successful efforts include providing institutional resources for family accommodations in the hospital (Franck, Ferguson, Fryda, & Rubin, 2015, socioemotional resources such as peer-to-peer parental support for NICU parents (Hall, Ryan, Beatty, & Grubbs, 2015;Macdonell et al, 2013;, psychological resources from mental health professionals , and even financial resources to promote optimal infant nutrition through breastfeeding in the NICU (Johnson et al, 2018;Morgan et al, 2015;Relton et al, 2018). Well-established parent education programs increase caregiver skills and knowledge; reduce parental distress, depression, and anxiety; and strengthen the parentinfant relationship in the NICU (Chertok, McCrone, Parker, & Leslie, 2014).…”
Section: Implications For Neonatal Research Practice and Policymentioning
confidence: 99%